Safrana l Prevents Prostate Cancer Recurrence by Blocking the Re-activation of Quiescent Cancer Cells via Downregulation of S-Phase Kinase-Associated Protein 2 - Jiang, Xue; Li, Yang; Feng, Ji-ling; Nik Nabil, Wan Najbah; Wu, Rong; Lu, Yue; Liu, Hua; Xi, Zhi-chao; Xu, Hong-xi (Frontiers in Cell and Developmental Biology, 2020)
Re-proliferation of quiescent cancer cells (QCCs) is considered to be the primary contributor to prostate cancer (Pca) recurrence and progression. In this study, we investigated the inhibitory effect of Safranal, a monoterpene aldehyde isolated from Crocus sativus (Saffron), on the re-proliferation of quiescent Pca cells in vitro and in vivo. Results showed that Safranal efficiently blocked the re-activation of quiescent Pca cells by downregulating the G0/G1 cell cycle regulatory proteins CDK2, CDK4, CDK6, phospho-Rb at Ser807/811 and elevating the levels of cyclin-dependent kinase (CDK) inhibitors, p21 and p27. Further investigation on the underlying mechanisms revealed that Safranal suppressed mRNA and protein expression levels of Skp2, possibly through the deregulation of the transcriptional activity of two major transcriptional factors, E2F1 and NF-κB subunits. Moreover, safranal inhibited AKT phosphorylation at Ser473 and deregulated both canonical and non-canonical NF-κB signaling pathways. Safranal suppressed the tumor growth of quiescent Pca cell xenografts in vivo. Furthermore, safranal-treated tumor tissues exhibited a reduction in Skp2, E2F1, NF-κB p65, p-IκBα (Ser32), c-MYC, p-Rb (Ser807), CDK4, CDK6, CDK2, and elevation of p27 and p21 protein levels. Therefore, our findings demonstrate that Safranal suppresses cell cycle re-entry of quiescent Pca cells in vitro and in vivo plausibly by repressing the transcriptional activity of two major transcriptional activators of Skp2, namely E2F1 and NF-κB, through a downregulation of AKT phosphorylation and NF-κB signaling pathways, respectively.